Methodologies For Measuring Agricultural Price Interventions Effects. (Washington, 1980)
This paper describes the use of micro-economic, informal methodologies in six country case studies (Argentina, Egypt, Kenya, Pakistan, Thailand and Yugoslavia) and in subsequent additional analysis. The research has confirmed that there is extensive intervention with market forces by governments in LDC, which has turned the domestic terms of trade against agriculture and has significant efficiency and income distribution effects.
Keywords: Agricultural Prices Mathematical Models